Interfaith Harmony and Digital Media: A Study of the Dissemination of Islamic Solidarity Values through Podcast - Putri Naeli Muna; Gina Arum Riski; Tsuaibatul Aslamiyah; Wieldan Sigit Diarto; Majd Finy Kurniawan; Mar'atus Sholikhah; Rizal Kurniawan (International Tatho Academics, 2026)
The purpose of this study is to explore the values of Islamic brotherhood (ukhuwah) in the context of interfaith dialogue in the podcast “Log-In” hosted by Dedy Corbuzier. This qualitative research in the form of media observation uses content analysis. The results of this study found the dissemination of Islamic brotherhood values in the podcast ‘Log-In’ hosted by Dedy Corbuzier, such as the values of ukhuwah basyariah (tolerance and inclusive attitudes) and ukhuwah watoniah (commitment to building constructive dialogue between religious communities in building a civilised nation). The contribution of this research emphasises that podcasts can be an effective digital medium for strengthening brotherhood among religious communities.